K problematice ustálených verbo-nominálních jednotek v biblické frazeologii ve vztahu k jejich původu a evropskému kontextu: na příkladě výrazu „mít víru“ - Načeva-Marvanová, Mira (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The study examines biblical phraseology as a cultural-historical phenomenon in which the original biblical texts have, over many centuries and generations, transferred both traditional phraseological units and structural established patterns of constructions, such as some verb phrases with abstract nouns, into the languages of the Bible’s translations. Already present in the original Byzantine Greek text, they are distinguished by their idiomatic nature and represent the so-called quasi-phraseological units. Units of this kind could be formed usually by frequently used words, such as some verbs with a tendency to desemantization like the verbs “have”, “get”, “give”, as well as commonly used and well-known abstract nouns like “faith”, “hope”, “feeling” etc. Their occurrence has subsequently been accepted and reduplicated in a number of languages as it is evident from the first translation efforts through early Renaissance and humanist versions. The use of such idiomatic structures has penetrated spontaneously from the language of the canonical texts into the common standard.